Dhamma Arunachala: An Exemplary Self-Efficient and Self-Sufficient Centre - Shakya , Sujata; Bajrachrya, Sameer Ratna (MAJ - Malaysia Architectural Journal, 2025)
Climate Responsive Design is a key to developing resiliency in response to changing circumstances and unpredictable calamities due to climate change. In the Urban Context, architects are designing buildings with lack of co-relation between built spaces and natural environment, which is an unsustainable approach. The urban centres are developed in such a way that the services of facilities heavily depend on the market, consequently developing unsustainable culture. As a learning from our traditional lifestyle, we need to design a city responding to the natural surroundings and local resources rather than replicating rampant concrete jungles. We need to develop permaculture as a source of self-reliant economy in parallel with the other economic sources as well as improvise indigenous construction technologies with innovative ideas. There is a huge research gap between Indigenous ways of construction practices aided by contextual ‘learning by doing’ and the modern trend of construction. Filling the gap helps develop Self- sufficient Sustainable cities and provide adequate answers to complex challenges like climate change, natural disasters, pandemic situations etc. From the empirical perspective, it is difficult to achieve a complete balance between ecology and the human density in an urban context. However, there are some exemplary premises such as: Dhamma Arunachala, a Vipassana Meditation Centre in Tiruvannamalai, Tamilnadu, India. Located in Hot Equatorial region where temperature goes to above 35 Degree Celsius, the centre presents itself as an example of alternative ways of construction practices, application of Passive Cooling Technique, Food Production and Waste Water Management that makes the whole Centre Self Sufficient and Efficient.